السياحة البيئية مدخل حديث للإسهام في تحقيق التنمية المستدامة - بن خديجة منصف; أولاد زاوي عبد الرحمان (My University, 2016)
الملخَّـص: يلعب الإستثمار السياحي دورا مهما في دفع عملية النمو وتنشيط ديناميكية البناء الهيكلي إقتصاديا؛ إجتماعيا وثقافيا، وعلى الرغم من النتائج الإيجابية التي يحققها هذا القطاع إلا أن الإستعمال غير العقلاني للثروات الطبيعية والإضرار بحق جيل المستقبل من جهة؛ والمناداة بحماية وصيانة البيئة من جهة أخرى، دعيا إلى ضرورة التركيز على سياحة بيئية نظيفة رفيقة بالبيئة وصديقة للمجتمع، من خلال التوعية والتثقيف البيئي للسياح والعاملين والسكان المحليين، وبذلك أصبحت السياحة البيئية كثقافة وسلوك أخلاقي يدعّمان كثيرا تحقيق التنمية المستدامة. Abstract: Touristic investment plays important role in pushing development activate structural dynamism, economic, socially and cultural, dispite, the positive result which realised by this sector, the non rational use of natural wealth and damage ( harm) by the right of future generation from one hand, other hand calling for protection and maintaing environment, leads to focus on environment tourism, clean and friendly with the environment and society, through awareness and cultivate of tourists, employment and local habitants environmently, so that environment tourism became as culture and moral behavior support sustainable development.